EVALUASI PELAKSANAAN PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) DI DESA PAGARAN TAPAH KECAMATAN PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - Sari, Wella; Yusmini, Yusmini; Edwina, Susy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims are to know implementation of rural agribusiness development program (PUAP) and to compare the income of members Gapoktan before and after the programin Pagaran Tapah village Pagaran Tapah Darussalam District of Rokan Hulu Regency. The population of this research is a member of Sokun Tani Mandiri Gapoktan who get loan PUAPfunds in 2012, 2013 and 2014, by using Purposive sampling method total sample obtained are 31 peoples.Data analysis using GAP Analysis to evaluate the implementation of the programme with the success indicators of PUAP program (inputs, processes, outputs and outcomes) and to compare the income of Gapoktan members using the analysis of farming before and after PUAP program.The results showed the implementation of the program PUAP in Pagaran Tapah Village goes well with the total average of GAP value is 2,95 (R<3) and income of each Gapoktan members has increased after the program caused by production increased, price fluctuations, and scaling up efforts. where an increase in real incomeof palm oil maintenance farmers who got PUAP funds in 2012,2013, and 2014 are 28,69%, 35,35%, and 24,93%. For home industry who got PUAP funds in 2012 and 2013 are 33,04% and 37,00%, for fish farmers who got PUAP funds in 2013 and 2014 is 53,41% and 39,47%. The last for cattle raiser who got PUAP funds in 2013 and 2014 an increase in real income are 8,23% and 33,38%. Keywords : evaluation, PUAP program, GAP Analysis